Uranium adsorption electrostatic spinning membrane as well as preparation method and application thereof

By preparing uranium adsorption electrospinning film with high specific surface area and porosity, the problem of insufficient uranium adsorption performance and adsorption capacity in seawater is solved, and the efficient uranium adsorption effect in low-uranium-concentrated seawater is achieved.

CN119411375AActive Publication Date: 2025-02-11BEIJING RESEARCH INSTITUTE OF CHEMICAL ENGINEERING AND METALLURGY
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202411530630.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-02-11
Estimated Expiration
2044-10-30

AI Technical Summary

Technical Problem

When the prior art extracts uranium in seawater, the uranium adsorption performance and adsorption capacity are insufficient, resulting in low resource development efficiency.

Method used

A preparation method of uranium adsorption electrospinning film is adopted, and a solution containing hydroxylamine hydrochloride and alkali metal carbonate is reacted with a solution of polyacrylonitrile to form an aminoxime-polymerized polyacrylonitrile film, and is prepared by electrospinning technology. The spinning film with high specific surface area and porosity is produced to improve its uranium adsorption performance.

Benefits of technology

The uranium adsorption performance and adsorption capacity of the electrospinned film are significantly improved, and the uranium adsorption efficiency is shown in particular in seawater with low uranium concentration, solving the problem of insufficient uranium adsorption performance in the prior art.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a uranium adsorption electrostatic spinning membrane as well as a preparation method and application thereof. The preparation method comprises the following steps: (1) adding a solution B containing hydroxylamine hydrochloride and alkali carbonate into a solution A containing polyacrylonitrile, and stirring to obtain a reaction product; centrifuging a reaction product, and taking supernatant liquid as a spinning solution; the mass ratio of the polyacrylonitrile to the hydroxylamine hydrochloride is 2: (2-3); (2) carrying out electrostatic spinning on the spinning solution to obtain an amidoximation polyacrylonitrile membrane; (3) soaking the amidoximation polyacrylonitrile membrane in an alkali metal hydroxide solution; and soaking the amine oximation polyacrylonitrile membrane subjected to alkali treatment in water to obtain the uranium adsorption electrostatic spinning membrane. According to the preparation method, the utilization rate of raw materials can be increased, and the uranium adsorption performance of the electrostatic spinning membrane is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a uranium adsorption electrostatic spinning membrane and a preparation method and application thereof. Background Art

[0002] Uranium resources are of great significance to the industrial, agricultural and military fields, and are also an important foundation for the development of nuclear energy. At present, uranium resources mainly come from land mines, but my country's land uranium resources are relatively scarce, and there are certain difficulties in the development of uranium resources. Uranium resources are abundant in seawater, so it is of great significance to develop efficient and economical methods for extracting uranium from seawater. Among the many methods for extracting uranium from seawater, the adsorption method has good adsorption selectivity, high adsorption capacity, simple operation and low cost, and is considered to be one of the more promising methods for extracting uranium from seawater. Summary of the invention

[0003] One object of the present invention is to provide a method for preparing a uranium adsorption electrostatic spinning membrane, which can improve the utilization rate of raw materials and improve the uranium adsorption performance of the electrostatic spinning membrane. Another object of the present invention is to provide a uranium adsorption electrostatic spinning membrane. Another object of the present invention is to provide a use of a uranium adsorption electrostatic spinning membrane.

[0004] In one aspect, the present invention provides a method for preparing a uranium adsorption electrospinning membrane, comprising the following steps:

[0005] (1) adding a solution B containing hydroxylamine hydrochloride and an alkali metal carbonate to a solution A containing polyacrylonitrile, and then stirring at 60 to 80° C. for 40 to 60 hours to obtain a reaction product; centrifuging the reaction product, and taking the supernatant as a spinning solution; the mass ratio of the polyacrylonitrile to the hydroxylamine hydrochloride is 2:(2 to 3);

[0006] (2) electrospinning the spinning solution to obtain an amine oxime polyacrylonitrile membrane; wherein the spinning solution injection speed is 0.5 to 15 mL / h, the voltage of the spinning electrode end is 15 to 50 kV, the voltage of the receiving end is -5 to -0.5 kV or the receiving end is grounded, and the distance between the receiving end and the spinning electrode end is 10 to 60 cm;

[0007] (3) soaking the amine oxime polyacrylonitrile membrane in an alkali metal hydroxide solution with a concentration of 0.005-0.04 mol / L, and reacting it at 40-60° C. for 2-8 hours; then soaking the alkali-treated amine oxime polyacrylonitrile membrane in water to obtain a uranium adsorption electrospinning membrane.

[0008] The invention firstly amines polyacrylonitrile and then performs spinning. Compared with the method of first spinning polyacrylonitrile and then amines polyacrylonitrile fiber, the preparation method of the invention can improve the utilization efficiency of hydroxylamine hydrochloride and improve the adsorption performance of electrostatic spinning membrane for uranium.

[0009] According to the preparation method of the present invention, preferably, the solvent in solution A is selected from one or more of N,N-dimethylformamide, N,N-dimethylacetamide, and tetrahydrofuran, and the solvent in solution B is selected from one or more of N,N-dimethylformamide, N,N-dimethylacetamide, and tetrahydrofuran;

[0010] In solution A, the concentration of polyacrylonitrile is 0.1 to 0.5 g / mL;

[0011] In solution B, the concentration of hydroxylamine hydrochloride is 0.2 to 0.3 g / mL.

[0012] More preferably, the solvent in solution A is N,N-dimethylformamide. More preferably, the concentration of polyacrylonitrile in solution A is 0.2-0.3 g / mL.

[0013] In certain embodiments, the method further comprises the step of preparing solution A: dissolving polyacrylonitrile in a solvent and stirring to obtain solution A.

[0014] More preferably, the solvent in solution B is N,N-dimethylformamide. More preferably, the concentration of hydroxylamine hydrochloride in solution B is 0.25-0.28 g / mL.

[0015] Preferably, the mass ratio of polyacrylonitrile to hydroxylamine hydrochloride is 2:(2.5-2.7). This can reduce the amount of raw materials used and improve the uranium adsorption capacity of the electrospun membrane in seawater with low uranium concentration.

[0016] According to the preparation method of the present invention, preferably, the mass ratio of hydroxylamine hydrochloride to alkali metal carbonate is 1:(1-3); the alkali metal carbonate is selected from one or more of sodium carbonate and potassium carbonate, and the alkali metal hydroxide is selected from one or more of potassium hydroxide and sodium hydroxide.

[0017] More preferably, the mass ratio of hydroxylamine hydrochloride to alkali metal carbonate is 1:(1.5-2). More preferably, the alkali metal carbonate is potassium carbonate. The potassium carbonate is anhydrous potassium carbonate.

[0018] In some embodiments, the method further comprises the step of preparing solution B: adding hydroxylamine hydrochloride to the solvent, stirring to dissolve the hydroxylamine hydrochloride, adding alkali metal carbonate, and stirring at 20 to 38° C., preferably at 25 to 30° C., for 2 to 8 hours, preferably for 3 to 5 hours.

[0019] Preferably, the solution B containing hydroxylamine hydrochloride and alkali metal carbonate is added to the solution A containing polyacrylonitrile, and then stirred at 70-75° C. for 45-50 hours to obtain a reaction product.

[0020] Preferably, the reaction product is centrifuged using a centrifuge.

[0021] According to the preparation method of the present invention, preferably, pneumatically assisted electrospinning or electrospinning by wire electrode is used. According to one embodiment of the present invention, pneumatically assisted electrospinning is used.

[0022] According to the preparation method of the present invention, preferably, the spinning solution injection speed is 8-12 mL / L, the spinning electrode terminal voltage is 15-25 kV, the receiving end voltage is -2--1 kV, and the distance between the receiving end and the spinning electrode terminal is 40-50 cm.

[0023] According to the preparation method of the present invention, preferably, the spinning solution injection speed is 1-2 mL / L, the spinning electrode terminal voltage is 35-40 kV, the receiving end is grounded, and the distance between the receiving end and the spinning electrode terminal is 20-30 cm.

[0024] The spinning conditions of the present invention can obtain a spinning fiber membrane with large specific surface area, high porosity and high strength.

[0025] Preferably, the concentration of the alkali metal hydroxide solution is 0.01-0.02 mol / L. The alkali metal hydroxide is selected from one or more of potassium hydroxide and sodium hydroxide, preferably potassium hydroxide.

[0026] Preferably, the amine oxime polyacrylonitrile membrane is reacted with an alkali metal hydroxide solution at 50 to 55° C. for 4 to 5 hours.

[0027] On the other hand, the present invention provides a uranium adsorption electrostatic spinning membrane, which is prepared by the above method.

[0028] In another aspect, the present invention provides use of the uranium adsorption electrospinning membrane in extracting uranium from water.

[0029] According to the use of the present invention, preferably, the water is selected from one or more of seawater and underground brine. Preferably, the water is seawater.

[0030] According to the use of the present invention, preferably, the concentration of uranium in water is 0.5 to 7 ppm. More preferably, the concentration of uranium in water is 2 to 5 ppm.

[0031] The uranium adsorption material of the present invention has good adsorption performance for uranium elements in low-concentration seawater and has a high adsorption capacity.

[0032] The preparation method of the present invention can improve the utilization efficiency of raw materials, improve the uranium adsorption performance and uranium adsorption capacity of the electrospinning membrane. The fiber membrane obtained by the preparation method of the present invention has a large specific surface area, high porosity, and high uranium adsorption capacity. DETAILED DESCRIPTION

[0033] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.

[0034] Example 1 and Comparative Example 1

[0035] (1) Dissolve 2 g of polyacrylonitrile in 10 mL of N,N-dimethylformamide and stir thoroughly to completely dissolve the polyacrylonitrile to obtain solution A. Add hydroxylamine hydrochloride to 10 mL of N,N-dimethylformamide and stir thoroughly to dissolve the polyacrylonitrile. Then, add anhydrous potassium carbonate and stir at 25°C for 4 h to obtain solution B.

[0036] Solution B was slowly poured into solution A, and the mixture was stirred at 70° C. for 48 hours to obtain a reaction product; the reaction product was centrifuged using a centrifuge, and the supernatant was taken as the spinning solution.

[0037] (2) The spinning solution was electrospun by pneumatic assistance to obtain an amine oxime polyacrylonitrile membrane. The spinning solution injection speed was set to 10 mL / h, the spinning electrode end voltage was 20 kV, the receiving end voltage was -1 kV, and the distance between the receiving end and the spinning electrode end was 50 cm.

[0038] (3) placing the amine oxime-treated polyacrylonitrile membrane in a potassium hydroxide solution with a concentration of 0.02 mol / L and reacting it at 50° C. for 5 hours; then soaking the alkali-treated amine oxime-treated polyacrylonitrile membrane in deionized water overnight to obtain a uranium adsorption electrospinning membrane.

[0039] The amounts of hydroxylamine hydrochloride and anhydrous potassium carbonate used are shown in Table 1.

[0040] Table 1

[0041] Example 1 Comparative Example 1 Amount of Hydroxylamine Hydrochloride (g) 2.6 1.3 Amount of anhydrous potassium carbonate (g) 5.2 2.6

[0042] Example 2

[0043] (1) Dissolve 2 g of polyacrylonitrile in 10 mL of N,N-dimethylformamide and stir thoroughly to completely dissolve the polyacrylonitrile to obtain solution A. Add 2.1 g of hydroxylamine hydrochloride to 10 mL of N,N-dimethylformamide and stir thoroughly to dissolve the polyacrylonitrile. Then, add 4.2 g of anhydrous potassium carbonate and stir at 25°C for 4 h to obtain solution B.

[0044] Solution B was slowly poured into solution A, and the mixture was stirred at 70° C. for 48 hours to obtain a reaction product; the reaction product was centrifuged using a centrifuge, and the supernatant was taken as the spinning solution.

[0045] (2) The spinning solution was electrospun through a wire electrode to obtain an amine oxime polyacrylonitrile membrane. The spinning solution injection speed was set to 1 mL / h, the spinning electrode end voltage was set to 40 kV, the receiving end was grounded, and the distance between the receiving end and the spinning electrode end was 20 cm.

[0046] (3) placing the amine oxime-treated polyacrylonitrile membrane in a potassium hydroxide solution with a concentration of 0.02 mol / L and reacting it at 50° C. for 5 hours; then soaking the alkali-treated amine oxime-treated polyacrylonitrile membrane in deionized water overnight to obtain a uranium adsorption electrospinning membrane.

[0047] Comparative Example 2

[0048] (1) Dissolve 2 g of polyacrylonitrile in 10 mL of N,N-dimethylformamide and stir thoroughly to completely dissolve the polyacrylonitrile to obtain a spinning solution.

[0049] (2) The spinning solution was electrospun through a wire electrode to obtain a polyacrylonitrile membrane. The spinning solution injection speed was set to 1 mL / h, the spinning electrode end voltage was set to 40 kV, the receiving end was grounded, and the distance between the receiving end and the spinning electrode end was 20 cm.

[0050] (3) 26 g of hydroxylamine hydrochloride was added to a mixed solution of 130 mL of deionized water and 130 mL of methanol, and sodium hydroxide was added to adjust the pH to neutral to obtain a reaction solution for amine oximation.

[0051] (4) Adding the polyacrylonitrile membrane to the amine oxime reaction solution and reacting at 70° C. for 48 hours to obtain the amine oxime polyacrylonitrile membrane.

[0052] (5) placing the amine oxime-treated polyacrylonitrile membrane in a potassium hydroxide solution with a concentration of 0.02 mol / L and reacting it at 50° C. for 5 hours; then soaking the alkali-treated amine oxime-treated polyacrylonitrile membrane in deionized water overnight to obtain a uranium adsorption electrospinning membrane.

[0053] Experimental example

[0054] The uranium adsorption electrospun membrane was placed in spiked seawater with a uranium concentration of 3.3 ppm, and then adsorbed on a shaker for 48 hours at a constant temperature of 25°C. After the adsorption, the sample was dried and the uranium adsorption capacity of the uranium adsorption electrospun membrane was tested by the digestion method. The results are shown in Table 2.

[0055] Table 2

[0056] Example 1 Comparative Example 1 Example 2 Comparative Example 2 Uranium adsorption capacity (mg U / g) 60.2 31.6 47.5 1.46

[0057] The present invention is not limited to the above-mentioned embodiments. Without departing from the essential content of the present invention, any deformation, improvement and substitution that can be conceived by those skilled in the art shall fall within the scope of the present invention.

Claims

1. A method for preparing a uranium adsorption electrospinning membrane, characterized in that: The steps include: (1) adding a solution B containing hydroxylamine hydrochloride and an alkali metal carbonate to a solution A containing polyacrylonitrile, and then stirring at 60 to 80° C. for 40 to 60 hours to obtain a reaction product; centrifuging the reaction product, and taking the supernatant as a spinning solution; the mass ratio of the polyacrylonitrile to the hydroxylamine hydrochloride is 2:(2 to 3); (2) electrospinning the spinning solution to obtain an amine oxime polyacrylonitrile membrane; wherein the spinning solution injection speed is 0.5 to 15 mL / h, the voltage of the spinning electrode end is 15 to 50 kV, the voltage of the receiving end is -5 to -0.5 kV or the receiving end is grounded, and the distance between the receiving end and the spinning electrode end is 10 to 60 cm; (3) soaking the amine oxime polyacrylonitrile membrane in an alkali metal hydroxide solution with a concentration of 0.005-0.04 mol / L, and reacting it at 40-60° C. for 2-8 hours; then soaking the alkali-treated amine oxime polyacrylonitrile membrane in water to obtain a uranium adsorption electrospinning membrane.

2. The preparation method according to claim 1, characterized in that: The solvent in solution A is selected from one or more of N,N-dimethylformamide, N,N-dimethylacetamide, and tetrahydrofuran, and the solvent in solution B is selected from one or more of N,N-dimethylformamide, N,N-dimethylacetamide, and tetrahydrofuran; In solution A, the concentration of polyacrylonitrile is 0.1 to 0.5 g / mL; In solution B, the concentration of hydroxylamine hydrochloride is 0.2 to 0.3 g / mL.

3. The preparation method according to claim 1, characterized in that: Electrospinning was performed by pneumatic assistance or by wire electrode electrospinning.

4. The preparation method according to claim 1, characterized in that: The spinning solution injection speed is 8-12 mL / L, the spinning electrode terminal voltage is 15-25 kV, the receiving end voltage is -2--1 kV, and the distance between the receiving end and the spinning electrode terminal is 40-50 cm.

5. The preparation method according to claim 1, characterized in that: The spinning solution injection speed is 1-2 mL / L, the spinning electrode terminal voltage is 35-40 kV, the receiving end is grounded, and the distance between the receiving end and the spinning electrode terminal is 20-30 cm.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The mass ratio of hydroxylamine hydrochloride to alkali metal carbonate is 1:(1-3); the alkali metal carbonate is selected from one or more of sodium carbonate and potassium carbonate, and the alkali metal hydroxide is selected from one or more of potassium hydroxide and sodium hydroxide.

7. A uranium adsorption electrospinning membrane, characterized in that: The uranium adsorption electrospinning membrane is prepared by the method according to any one of claims 1 to 6.

8. Use of the uranium adsorption electrospinning membrane according to claim 7 in extracting uranium from water.

9. The use according to claim 8, characterized in that The water is selected from one or more of seawater and underground brine.

10. The use according to claim 8, characterized in that The concentration of uranium in water is 0.5 to 7 ppm.

Citation Information

Patent Citations

  • Amidoximated polyacrylonitrile spinning solution and nanoscale ion exchange fiber prepared from solution

    CN105568423A

  • Nanofiber material for extracting uranium from seawater and preparation method of nano-fiber material

    CN107475798A

  • Shrinkage-resistant antibacterial nano composite fiber material for extracting uranium from seawater and preparation method of shrinkage-resistant antibacterial nano composite fiber material

    CN110846739A

  • Anti-biofouling hydrogel film material for extracting uranium from seawater and preparation method thereof

    CN112516975A

  • Amino and amidoxime polyacrylonitrile nanofiber as well as preparation method and application thereof

    CN113699620A